The Use of Reader’s Theater Strategy in Teaching Reading Comprehension for the Tenth Grade Students at SMK Negeri 3 Lubuklinggau - Novaliza, Sri; Seli, Sastika; Syafitri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The objective of this research was to know the influence of using reader’s theater strategy on reading comprehension for the tenth grad students at SMKN 3 Lubuklinggau academic year 2024/2025. The researcher used pre-experimental method and the data were collected through test multiple choice. The population of this study was all of the tenth grade computer and networking engineering (TKJ) students of SMKN 3 Lubuklinggau academic year 2024/2025 consisted of 105 students and devided into three classes. The sample was taken through purposive sampling, it was class tenth TKJ 2 with 35 students. The researcher used three technique namely individual score, normality testing, and paired t-test in analyzing the data. The students’ average score in the pre-test was 52.43, whereas in the post-test, the students’ average score was 78.57. The students’ average score in the post-test was higher than the students’ score in the pre-test. The t-obtained was 11.47, it was higher than 2.032 as critial value. It means that reader’s theater strategy is significantly positive influence in teaching reading comprehension for the tenth grade students at SMKN 3 Lubuklinggau academic year 2024/2025. Keywords: Narrative Text, Reading Comprehension, Reader’s Theater Strategy.